Dukun Adat sebagai Benteng Pendidikan Karakter Pemuda Desa Adat Tengger, Ngadas, Kabupaten Malang - Maulida, Faishal Hilmy (Academy of Education Journal, 2024)
This study aims to explore how the Tengger Indigenous community in Ngadas Village, Malang Regency, preserves their traditions amidst the challenges of modernization. The research employs a historical method, which includes four primary stages: (1) heuristic, involving the collection of data through books, journal articles, newspapers, as well as interviews and field observations; (2) verification, focusing on the credibility evaluation of sources by conducting source criticism; (3) interpretation, or the process of data interpretation; and (4) historiography, related to how the data is presented. The findings of this research highlight the crucial role of traditional healers as informal leaders who are responsible not only for religious rituals but also for addressing social issues in the community and educating the young generation with positive character values. The study concludes that traditional healers play a key role in integrating tradition with the changes of the times, and that the traditional farming practices of the Tengger community are not only their main source of livelihood but also a means to shield the community from the negative impacts of modernization.